Perbaikan Tata Letak Fasilitas Departemen Sheet Metal 1 PT. MCP - Pramono, Meylinda; Widyadana, I Gede Agus (Jurnal Titra, 2015)
Improvements layout on the sheet metal 1 department at PT. MCP held 45.89% due to backtracking that occurs when the operator does the production process. This improvement layout is built to match better layout for PT. MCP. The method used is the method of calculation of the moment without any cost calculation. Total moment of initial layout is 1,785,988.5. Improvement facility layout on sheet metal 1 department uses two methods. 2-Opt and CRAFT are both the methods. Calculations for 2-Opt method does not produce a total of better moment than the moment of the first layout, but the percentage of backtracking decrease to 38.95%. 2-Opt layout still can not be applied to the real situation because the moment is used as a reference. Otherwise total moment of CRAFT method generate better moment than the moment of the initial layout that is equal to 1,656,291.8 and percentage of backtracking also decreased to 23,69%. Layout CRAFT produced by the method can be applied to the real situation in the department of sheet metal 1 PT. MCP.